Socioeconomic Relations with the Utilization of Maternal Health Services in Marginalized Communities - Syaekhu, Ahmad; ., Djohar; Syahadad, Susanti I Mutiah; ., Irma; Idrus, Hasta Handayani (Journal of Ecohumanism, 2025)
This study aims to see the description of the utilization of maternal health services in marginalized communities in Makassar City and its relationship with socioeconomic characteristics. The total respondents who returned the complete questionnaire were 560 people or 79.6% of the 783 total questionnaires distributed. The study was conducted cross-sectionally. To describe socioeconomic and utilization of health services using frequency distribution. We set using cross-tabulations to see the relationship between the two variables. The results showed that socioeconomic characteristics have a significant relationship with the utilization of maternal and child health services. This study shows that the low utilization of maternal health services in vulnerable groups such as women can be caused by factors such as low levels of education, income, and accessibility of health services.